Virus Infections and Interferon Inductors in the Complex Therapy - M. G. Romantsov; F. I. Ershov; A. L. Kovalenko; D. S. Sukhanov; O. M. Liberanskaya (Антибиотики и Химиотерапия)
Interferon inductors of various chemical groups, belonging to antivirals, and induction of several types of endogenous interferon in blood serum are described. Cycloferon was shown efficient in the complex treatment of chronic hepatitis C, tuberculosis in HIV-infected subjects, arbovirus diseases, influenza and acute respiratory virus infections.